Circular economy and food waste problems in Indonesia: Lessons from the policies of leading Countries - Waluyo; Dona Budi Kharisma (Cogent Social Sciences)
Indonesia is the second largest food waste disposer after Saudi Arabia. The potential increase in waste and food waste is an essential issue for Indonesia, given the problem’s economic, social, and environmental implications. However, the implementation of the circular economy concept still faces various problems compared to Germany, Netherlands, and China.This paper aims to formulate an ideal policy to implement the circular economy concept through policy comparisons between countries especially to overcome the problem of food waste in Indonesia. This is legal politics research that takes a conceptual and comparative approach. A comparative study was conducted on circular economy policies relating to food waste in Indonesia, Germany, the Netherlands, and China. Data was collected through a literature study analyzing various circular economy regulations. According to the research findings, the Circular Economy Act has to be implemented in Germany, Netherlands, and China has been proven effective as a guideline and policy direction to provide solutions for the problems of waste and food waste. The Circular Economy Act serves as a guide and policy direction for the government, private sector, communities, and parties to address environmental issues and help realize sustainable development goals.